Studi Implementasi Kebijakan Kota Layak Anak (KLA) di Kota Pekanbaru - Mustiqowati Ummul Fithriyyah (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
The policy imlementation of children appropriate city known as (KLA) is intended as a real effort to unite children rights issues into the planning and construction of district / city. Children care development is basically a condition for the respect, protection and fulfillment of children's rights.The policy imlementation of children appropriate city known as (KLA) in Pekanbaru has been launched through the establishment of the Task Force, but yet there appears to be a significant change. In general it can be said that the issue of Children has not been a priority in policy and budgeting in Pekanbaru city government and child protection movement has not been done optimally. The changes are not expected to be significant. This research is to know "why The policy imlementation of children appropriate city known as (KLA) in Pekanbaru is not optimal?”Obstacles in The policy imlementation of children appropriate city known as (KLA) in Pekanbaru are as follows: (1) Program KLA has not been popular in the levels SKPD in Pekanbaru and institutionally SKPD still egosektoral making it difficult to integrate the issue of Children in the preparation of programs on education, and also the preparation of RAD -KLA, (2) implementing inadequate institutional capacity. (3) The absence of a budget based on the needs of children in the budget, (4) Not to achieve a partnership between government, private sector, community organizations, and the community itself, including children, in realizing Pekanbaru into the City of Eligible Children in accordance with the indicators specified in Peraturan Menteri Negara PPPA RI No. 12 in 2011.